Uncharted waters: mesenchymal stem cell treatment for pediatric refractory rheumatic diseases; a single center case series - Stephen C. Wong; Leah C. Medrano; Alice D. Hoftman; Olcay Y. Jones; Deborah K. McCurdy (BMC, 2021)
Abstract Background With the advent of innovative therapies including biologics and Janus kinase inhibitors, children with rheumatic diseases are more likely to have improved outcomes. Despite these advances, some children do not respond, or they, or their parents fear adverse events and seek other alternatives. Increasingly, private companies are offering mesenchymal stem cells (MSC) as an alternative, which are described as natural therapies for rheumatic diseases, often insinuating them as a cure. MSC have immunomodulatory properties, and transplantation of these stem cells have been used to successfully treat immunologic conditions like graft-versus-host disease. Lately, MSC research in adult lupus has been encouraging, but the clinical trials are still underway and in most, MSC therapy is not a standalone treatment. This retrospective case series will highlight three cases of pediatric refractory autoimmune disease whose parents sought out and received MSC therapy as a self-decision without first seeking medical advice from our specialty. The three families felt that their children were improved and in two believed that their child was cured. MSC have the potential of beneficial immunomodulation and may be a powerful tool in the therapy of rheumatic disease, but well controlled clinical trials are necessary and should be designed and monitored by experts in childhood rheumatic disease. Case presentation Three children with three different rheumatic diseases; systemic lupus erythematosus, mixed connective tissue disease and juvenile idiopathic arthritis were under the care of pediatric rheumatology at a large, tertiary-care, teaching institution. Multiple non-biologic and biologic disease-modifying anti-rheumatic drugs failed to significantly decrease disease activity, and as a result, the families chose to undergo MSC therapy. After transplantation, all children improved per patient and parent report and tapered off conventional immunosuppressive drugs. No serious adverse events occurred in these three patients. Conclusion The three cases presented in this report reflect comparable beneficial outcomes and minimal risks published in adult studies. These were not controlled studies, however, and benefit was reported rather than documented. These cases suggest that MSC transplantation may prove a promising adjunctive treatment option; however, further research, development of standardized infusion therapy protocols, and well-designed monitored clinical trials are essential.